Caveat Emptor : The computable general equilibrium approach to assessing the poverty impact of trade liberalisation /: The computable general equilibrium approach to assessing the poverty impact of trade liberalisation. (December 2007) - Kirkpatrick, C. H (Colin H.), 1944-; Scrieciu, S. Serban
No abstract available